Role of integrated nutrient management for enhancing nitrogen use effi ciency in crop - Begizew Golla (Open Journal of Plant Science - Peertechz Publications, 2020)
Nitrogen is the most limiting nutrient for crop production in many of the world's agricultural areas and its effi cient use is important for the economic sustainability of cropping systems. In the past several years, the application of synthetic Nitrogen (N) fertilizer to farmland resulted in a dramatic increase in crop yields but with considerable negative impacts on the environment. Furthermore, the dynamic nature of N and its tendency for loss from soil‐plant systems creates a challenge for its effi cient management. New solutions were therefore needed to reduce N loss and to maximize the nitrogen use effi ciency with a simultaneous increase in crop yield. Studies undertaken so far on enhancing the NUE have emphasized integrated utrient management (conjoint use of inorganic fertilizers, organic fertilizers and biofertilizers) and other management practices involving the right source, time, rate and method of application. This review paper discusses N dynamics in soil‐plant systems and outlines the possibilities of enhancing Nitrogen-Use Effi ciency (NUE) through different Integrated Nutrient Management (INM) approaches.